Guatemala: The role of media in the public debate - Monzón, Ana Silvia (2018)
The article briefly presents some categories that guide the exposure, placing the concept of debate or public opinion centered on the media, and linking it with Guatemalan history in the last three decades. This period covers the formal end of the internal armed conflict towards 1985, the signing of the Peace Agreements in 1996, which opened the expectation of an effective democratization of institutions, citizenship and, of course, the media, until then very limited in the exercise of investigative and critical journalism, and the deterioration of state institutions that, especially in the last five years have begun to have an impact on critical public opinion (alternative and independent media), and have reinforced a scheme of collusion between the interests of political parties and the media, which has contributed to pervert democracy in the country.